Survivor Tales: Feminist Graphics Bridging Consciousness Raising into Reality - Croswell, Kimberly (International Journal for Talent Development and Creativity, 2024)
This article examines two feminist comic representations of violence against women founded in the lived experiences of artists Sabrina Jones, and Rebecca Migdal, editors with the annual graphic anthology World War 3 Illustrated. In these visual narratives, the reader is introduced to the impact violence, visible and invisible, has on these women’s lives as they recollect events, and move on from their painful experiences. Far from offering a commiseration of pain, a function which Susan Sonntag attributes to disaster and war photography in Regarding the pain of others, these graphics (or comics) project empathy, while also empowering readers by providing a sense of ‘what’s next?’ Also embedded in this analysis is an examination of the cultural roots of misogyny, through which violence against women and gendered ‘others’ is operationalised. Through their multimodal visual and narrative retelling of the harmful impact violence and the threat of violence had on their lives, Jones’ and Migdal’s graphics offer resolution and an opportunity for consciousness raising about the issues facing survivors of male violence. Their resistance gives voice to the experience of threats and abuse, and shares wisdom throughout it all.